Universal Fab-Fc masked cytokine prodrug platform: αPD-L1/IL-15 prodrug activates CD44+ CD8+ T cells in tumor-draining lymph nodes to enhance antitumor immunity - Wei Li; Ying Qin; Zejian Wang; Luyao Song; Gen Qi; Wenqiang Shi; Qiongya Zeng; Zilan Song; Ao Zhang; Huili Lu (Journal for ImmunoTherapy of Cancer)
Background Immunocytokines targeting immune checkpoints have shown great potential in overcoming resistance to immune checkpoint blockade (ICB), making them a major focus of development in recent years. However, severe dose-limiting toxicity hindered their clinical application. Therefore, it is vital to develop versatile strategies to improve safety and elucidate the underlying mechanisms of resistance reversal for advancing immunocytokine therapy.Methods A general prodrug platform was established to construct interleukin (IL)-15 and IL-12-based immunocytokine prodrugs (P-T, P-Y, and P-Y-IL12). The efficacy of the masking strategy was validated by in vitro activity assays and in vivo safety evaluations. Antitumor efficacy of P-T was assessed in two murine cold tumor models. A comprehensive immune correlate analysis was conducted in the tumor and tumor-draining lymph node (TDLN) to identify key effector cells responsible for overcoming resistance, followed by further confirmation with egression of T cell blockade, surgical excision of TDLN, and adoptive transfer experiments. Finally, the synergistic antitumor effects of P-T with other ICB or HPK1 inhibitors were investigated.Results P-T or P-Y using steric hindrance from antibody moiety Fab and Fc shields IL-15 activity in circulation, and reactivates it on cleavage by tumor-specific proteases. The universality of this masking strategy is also applicable to IL-12. Compared with prior constructs, P-T and P-Y exhibit prolonged half-life and tumor retention, facilitating sustained intratumoral immune response. P-T demonstrates reduced systemic toxicity but better control of established tumors over the unmasked counterpart. CD44+ CD8+ T cells in TDLNs are identified as critical mediators of P-T’s efficacy: blockade of CD44+ CD8+ T cell trafficking into the tumor microenvironment (TME) markedly diminishes its antitumor effects. On P-T treatment, CD44+ CD8+ T cells exhibit enhanced proliferation in TDLNs and improved antitumor activity. Furthermore, P-T combined with other immunotherapies enhances antitumor effects by increasing CD44+ CD8+ T cells in TDLNs or promoting their infiltration into the TME.Conclusions The Fab and Fc-masked prodrug serves as a universal strategy for next-generation immunocytokines design, effectively addressing their dose-limiting toxicity. Additionally, leveraging immunocytokines to mobilize T cells in TDLNs offers a promising therapy option to overcome resistance to ICB and HPK1 inhibitors.